Mengenal Karakteristik Genetik Penyakit Degeneratif dan Pemeriksaan Molekuler serta Upaya Pencegahan melalui Produk Makanan Sehat - Fitria Diniah Janah Sayekti; Tasrif Ahmad; Sehan Astri Fani (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
Degenerative diseases are a global health problem with increasing prevalence, including in Indonesia. This disease can cause serious complications in vital organs such as the heart, kidneys, and brain. Therefore, preventive efforts are needed through education and nutritional innovation. This community service program aims to provide education on molecular examinations for degenerative diseases and introduce the Watermelon Lemonade innovation as preventive nutrition. The activity was carried out in Dukuh Branglor, Mancasan Village, with the pre-test method, educational presentation, Q&A, product demonstration, and post-test. The results of the activity showed an increase in public knowledge about hypertension and its examination, as well as high enthusiasm for the Watermelon Lemonade innovation. Based on the results of the activity, it can be seen that molecular examinations can be used to diagnose hypertension through analysis of genetic biomarkers, proteins, and metabolites, and the Watermelon Lemonade innovation has the potential to help lower blood pressure in hypertensive patients. The success of this program was shown by an increase in the average pre-test score of 58.46 to 86.67 in the post-test. The Wilcoxon test showed (p < 0.001), indicating a significant difference between the pre-test and post-test results and proving an increase in participant understanding. The questionnaire results showed a high level of satisfaction from participants with the delivery of materials, product manufacturing demonstrations, and practical benefits that can be applied in everyday life. The Watermelon Lemonade innovation is not only useful as an alternative to preventing hypertension, but also has the potential to be further developed as a health product based on natural ingredients.